Functional and correlative analysis of common endometrial cancer driver mutations - Brown, MW (2022)
Endometrial cancer is a growing concern with increasing incidence and mortality countering the downward trend observed in many other cancers. Despite recent advances in understanding, much remains unknown about endometrial cancer pathogenesis and the molecular mechanisms that drive its initiation and growth. This has led to worse outcomes for patients due to a lack of effective prediction of disease course and of effective targeted therapeutics, particularly when surgery is not possible or curative. One of the largest advancements in our understanding of endometrial cancer has come from increased mutational profiling of human tumours. These studies have highlighted manygenes exhibiting high rates of mutation as drivers of endometrial cancer, with one suchgene being FBXW7.